Microbial Air Contamination in an Intensive Care Unit - Chih-Yi Chang; Liang Tseng; Lung-Shih Yang (Intelektual Pustaka Media Utama, 2015)
Unit layout affects every aspect of intensive care services, including patient safety. A previous study has shown that patients admitted to beds adjacent to the sink and to the door of a large bayroom had the highest number of positive blood cultures and the highest blood culture incidence density, respectively. The present study measures microbial air contamination in a medical intensive care unit of a medical center in central Taiwan. Of the 17 rooms, 8 rooms with distinct physical environmental characteristics were selected. Sampling tests were conducted between December 2013 and February 2014 with a microbial air sampler (MAS-100NT). TSA was used for bacteria collection and DG18 for fungi collection. The overall average bacterial and fungal concentrations were 83CFU/m3 and 69CFU/m3, respectively. The ranges were between 8-354 CFU/m3 and 0-1468 CFU/m3, respectively. A significant difference was found in the bacterial concentration (p=.005) between different room locations. The highest concentration was found in the rooms located at the front end of the circulation (99 CFU/m3), while the lowest was found in the rooms located at the rear end of the circulation (55CFU/m3). Differences in fungal concentrations for different room locations did not reach statistical significance. In addition, differences in bacterial and fungal concentrations for rooms with different sink locations did not reach statistical significance. Even though the microbial concentrations generally complied with standards, the results may help designers and hospital administrators develop a healthier environment for patients.